2019
DOI: 10.1111/weng.12432
|View full text |Cite
|
Sign up to set email alerts
|

English and other languages in Italian advertising

Abstract: The presence of plurilingual practices involving the mixing of local and other languages is widely attested in advertising, mainly with English but also with other languages. Globalization processes have contributed to the global spread of English, but also to the blurring of linguistic and cultural boundaries, with translanguaging and transcultural practices becoming increasingly common. This study provides an investigation of print advertisements from a corpus collected from 2011 to 2018 from Italian magazin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 54 publications
0
9
0
1
Order By: Relevance
“…When a journalists' goal is to promote a product, an event, an idea, or a lifestyle, they tend to use English more than in other, perhaps more neutral, news reporting contexts. This is because English in these contexts indexes coolness, sophistication, and modernity, as several studies of advertising have already demonstrated (Androutsopoulos, 2012;Baumgardner, 2006Baumgardner, , 2008Baumgardner & Brown, 2012;Bhatia, 1992Bhatia, , 2000Bhatia, , 2006Bhatia, , 2019Martin, 2007;Vettorel & Franceschi, 2019). In this way, readers can imagine themselves as participating in whatever globalized lifestyle trends are being described, and indirectly advertised, to them.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…When a journalists' goal is to promote a product, an event, an idea, or a lifestyle, they tend to use English more than in other, perhaps more neutral, news reporting contexts. This is because English in these contexts indexes coolness, sophistication, and modernity, as several studies of advertising have already demonstrated (Androutsopoulos, 2012;Baumgardner, 2006Baumgardner, , 2008Baumgardner & Brown, 2012;Bhatia, 1992Bhatia, , 2000Bhatia, , 2006Bhatia, , 2019Martin, 2007;Vettorel & Franceschi, 2019). In this way, readers can imagine themselves as participating in whatever globalized lifestyle trends are being described, and indirectly advertised, to them.…”
Section: Discussionmentioning
confidence: 86%
“…Of course, it is not only the Italian context where English borrowings occur. Numerous scholars have analyzed English borrowings in both journalism (Amorim, Baltazar, & Soares, 2017; Androutsopoulos, 2013; Molek‐Kosakowska, 2012; Simon, 2016) and advertising (Androutsopoulos, 2013; Baumgardner & Brown, 2012; Kelly‐Holmes, 2000; Li, 2019; Vettorel & Franceschi, 2019), showing that usage of English within different global language contexts has specific functions. Scholars who have examined the mixing of English with Portuguese, Romanian, and Polish in journalistic discourse (Amorim et al., 2017; Molek‐Kosakowska, 2012; Simon, 2016, respectively) argue that English is used intentionally, therefore pragmatically, for various reasons.…”
Section: English Language Mixing In Journalism and Advertisingmentioning
confidence: 99%
See 2 more Smart Citations
“…The scientists draw attention on linguistic resources and patterns of responses [12] in bilinguals, follow the efficiency of various types of multilingual advertising means including borrowing, code switching, heteroglossia, meaningless infringements of foreign words, linguistic and cultural fetish [13]. Special focus is given to English as a global language [14], the role it plays in forming cultural and linguistic identity through bilingual advertising in various multilingual spaces found in the English-speaking [15], [16], [17]] and non-English-speaking countries [18], [19], [20].…”
Section: Related Workmentioning
confidence: 99%